Sistem Informasi Logistik PT Fajar Multiguna - MUHAMMAD EKO PUJIANTO; FAJAR NUGRAHA; BAGUS RIZKITA; Hendro Nugroho (Institut Teknologi Adhi Tama Surabaya, 2022)
PT Fajar Multiguna is a start-up company engaged in the Procurement of Government Goods/Services and Logistics for the delivery of procurement packages. Quite a lot of other companies that use this delivery service. The system that runs is still manual, there is no website to track the whereabouts of packages that are in transit. An information system is needed to make it easier for customers to track shipments. For this reason, a web-based Logistics Information system was designed with the Laravel PHP framework programming language. This information system will make it easier for PT Fajar Multiguna’s customers to track the delivery of their packages, on the other hand PT Fajar Multiguna will also find it easier to handle the delivery data.